THE HALLOWEEN EFFECT IN EUROPEAN SECTORS - Oliveira, L.; Curto, J.; Carrazedo, T. (8th annual meeting of the PEJ, 2014)
We present economically and statistically empirical evidence that the Halloween effect is significant. A trading strategy based on this anomaly works persistently and outperforms the Buy and Hold Strategy in 8 out of 10 Indices in our sample. We present evidence that the Halloween strategy works every two out of three calendar years and if an investor followed it “blindly”, would yield an annual average excess of return of about 2,3% compared to the Buy and Hold strategy and further assure a significant eduction in risk in all the Indices (around 7,5% on an annual basis). We have considered several possible explanations for the anomaly, but none was able to completely justify the seasonal effect. We suggest that a possible explanation may be related with the negative average returns during the May–October period, rather than with a superior performance during the November–April period.